2017
DOI: 10.1186/s12893-017-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequential organ failure assessment score predicts mortality after coronary artery bypass grafting

Abstract: BackgroundMortality after coronary artery bypass grafting (CABG) is generally associated with underlying disease and surgical factors overlooked in preoperative prognostic models. Sequential Organ Failure Assessment (SOFA) and Acute Physiology and Chronic Health Evaluation (APACHE II) scores are widely used in intensive care units for outcome prediction. This study investigated the accuracy of these models in predicting mortality.MethodsBetween January 2010 and April 2013, 483 patients who underwent isolated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
(30 reference statements)
1
12
0
5
Order By: Relevance
“…30,31 We found that VIS max measured on the 1st postoperative day predicted mortality up to 1 yr, while most earlier studies reported only in-ICU, in-hospital, and 30-day mortality. 1,2,8,32,33 The findings of the current study showed relatively low mortality in the lowest three VIS max groups for up to 1 yr. 10,34 Higher vasoactive and inotropic medication doses were associated with short-term and intermediate-term mortality after cardiac surgery (Fig. 4).…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…30,31 We found that VIS max measured on the 1st postoperative day predicted mortality up to 1 yr, while most earlier studies reported only in-ICU, in-hospital, and 30-day mortality. 1,2,8,32,33 The findings of the current study showed relatively low mortality in the lowest three VIS max groups for up to 1 yr. 10,34 Higher vasoactive and inotropic medication doses were associated with short-term and intermediate-term mortality after cardiac surgery (Fig. 4).…”
Section: Discussionsupporting
confidence: 46%
“…Traditional ICU scoring systems were initially developed and validated for general ICU patients, 2 and then studied in cardiac surgery patients. 1,3,6 Those scoring systems measure multiple organ dysfunction in critically ill patients, and only roughly quantitate pharmacological cardiovascular system support. In the early postoperative period after cardiac surgery, patients with a poor prognosis often do not manifest dysfunction of other organs to the same extent as they have cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations